Research on competitive adsorption characteristics of CO2 and CH4 in coal - Zhipeng ZHAO; Yuzhe XIAO; Hongping LI; Bingbing JIA; Liming QIU; Feng SHEN; Dazhao SONG; Zhenlei LI; Shengquan HE (Meikuang Anquan, 2025)
Deep understanding of the competitive adsorption characteristics of CO2 and CH4 in coal seams is of great significance for achieving stable CO2 storage and efficient CH4 recovery. This study studies the competitive adsorption characteristics of CO2 and CH4 in coal under different conditions based on the CO2 and CH4 competitive adsorption experimental system. The results showed that the adsorption rate of CO2 was faster than that of CH4 in single-component adsorption, and the coal body reached the saturation adsorption state more quickly. Under the effect of larger concentration gradient, CH4 can reverse displace the adsorbed CO2, but the displacing time is longer than that of CO2 displacing CH4. The competitive adsorption capacity of CO2 in the coal is stronger than that of CH4. Based on the boundary of 30 ℃, too low or too high temperature will reduce the gas adsorption rate and prolong the competitive adsorption process of CO2 and CH4 in the coal. The increase of gas injection flow rate makes the total gas pressure increase, which leads to the shortening of the competitive adsorption process. When the proportion of dominant adsorption gas in the gas composition is lower than that of weak adsorption gas, the competitive adsorption process will be inhibited, and vice versa, it will promote the process to be completed faster.